STAGES OF TECHNICAL REVOLUTION AND ITS SOCIO-PHILOSOPHICAL IMPORTANCE - Abdullaevich, Kushakov Fayzulla (Journal of Higher Education and Academic Advancement, 2024)
This article examines the transformative discoveries in production, industry, and technology from the 17th to the 20th centuries, highlighting their profound impact on human life. General Background: The period marked a pivotal shift in economic and political relations, often referred to as the "big bang" of European industrialization, which catalyzed unprecedented advancements. Specific Background: Key developments in manufacturing machinery, automation, and computing are analyzed, revealing a trajectory of revolutionary change that reshaped labor, productivity, and societal structures. Knowledge Gap: Despite extensive research on individual technological innovations, there is a lack of comprehensive studies connecting these advancements to broader socio-economic transformations. Aims: This article aims to bridge this gap by situating technological progress within the context of evolving economic and political frameworks. Results: Findings indicate that the interplay between technological innovation and socio-economic change facilitated the emergence of new economic paradigms, contributing to both local and global shifts in power dynamics. Novelty: This study introduces a holistic perspective that integrates technological advancements with the evolution of economic relations, offering a fresh lens through which to understand the interconnectedness of industry and society. Implications: The insights gained from this research have significant implications for contemporary discussions on the relationship between technology and socio-economic development, suggesting that current technological trends may similarly reshape future economic landscapes.